The load performance of multi-level alternating voltage provided by upgrade effect - Can, Erol (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this paper, the applications of the multi-level inverter with a partial inductor are investigated on different loads. The operation of the inverter is given according to different conditions of the circuit at the six-part duty times. Mathematical equations for the inverter are forming according to the load which is resistive (R), inductive (L), and Capacitive (C) in serial connection. After describing the circuit structure, Matlab SIMULİNK also simulates the circuit for loads that are RLC, and a single-phase asynchronous motor. While the voltage and current measurements for the RLC load are performed; measurements of the main winding current, auxiliary winding current, electromagnetic torque, speed are made on the asynchronous motor. RLC loads are operated at high current values such as 297A in order to examine the suitability of the proposed system for systems that may require high current. When the current harmonic distortions of RLC loads are observed, the distortion values are acceptable values that are lower than % 5 that is international standards of the IEEE. In another hand, despite the voltage is insufficient for supplying the motor at the motor application, the voltage is upgraded with the boost effect of the inverter. So, the voltage is both a multilevel and sufficient. According to the obtained results, it is shown that multi-level inverter design has been successfully performed by using partial inductor source.